Optimizing EAP Course Design for Reading and Writing Development - Naumoska, Aneta; Naumoska Sarakinska, Biljana (University of Niš, Serbia, 2025)
This paper examines the differences between General English and English for Academic Purposes, exemplified by the specialized approaches and objectives of the latter in preparing learners for academic and professional success. It underscores the criticality of needs analysis in English for Academic Purposes, for tailoring instruction to academic goals and professional demands, contrasting it with the simpler applications in General English. Pedagogical strategies in English for Academic Purposes, such as genre-based instruction and the use of authentic, context-specific materials, address the limitations of standardized resources, fostering reflective practice and discipline-specific communication skills, while teachers navigate dual roles as linguistic and subject-matter facilitators, often working with students possessing greater subject knowledge. A sample curriculum design and writing task are presented, focusing on critical reading and synthesis to enhance cognitive and linguistic proficiency in writing. Course designers for English for Academic Purposes can gain insight from this paper as it highlights its transformative potential to prepare learners for globalized academic and professional challenges.
Keywords: English for Academic Purposes, course design, reading, writing